Using Puppet Games in Teaching Speaking for Tenth Graders of Senior High School - Dania Yolanda; Muhamad Sofian Hadi (English Language in Focus (ELIF), 2019)
This research aimed to improve the students’ speaking skill in English lesson by puppets games. This research was conducted by using Quasi-Experimental. The subject of this research was Class X MIPA of SMA Perjuangan Depok 2018/2019 academic year, which consisted of 29 students. The objective of this research was to teaching students’ speaking skill in English Lesson by using Puppets Games at Ten Grade of SMA Perjuangan Depok. The data were gathered through quantitative and qualitative data. The result of this research showed that there was increasing of students in speaking skill. The mean of pre-test was 58.34. The mean of post-test was 77. Based on the result analysis, it can be concluded that there was a significance using puppets games in teaching speaking at tenth grade senior high school. The result showed that the result of T-test calculation is 13.090 more higher than T-table 5%, it gained score 2.045. Therefore, it can be conclude that teaching speaking using puppets games is effective to improve speaking skill at the tenth grade of SMA Perjuangan Depok. The results of this study are expected to be useful to related parties such as principals, teachers, parents, students and further researchers.